DESIGN 3-PHASE 5-LEVELS DIODE CLAMPED MULTILEVEL INVERTER USING MATLAB SIMULINK - Ryanuargo, Ryanuargo; Setiyono, Setiyono (Jurnal Ilmiah Teknologi dan Rekayasa, 2016)
Today, The need for information continues to grow as advances in the world of technology and information. Information technology is getting almost inseparable from life, whether corporate, government, entertainment, etc. The one of the most technology used in recent years is multilevel inverters. The usage of these applications has become more diverse and affects a wide field of electrical engineering from a few watts to several hundred megawatts. One of the most multilevel inverters used nowadays is diode clamped multilevel inverters. The diode clamped inverter, particularly the three-level one, has drawn much interest in motor drive applications because it needs only one common voltage source. Also, simple and efficient PWM algorithms have been developed for it, even if it has inherent unbalances dc-link capacitor voltage problem. In this thesis author has designed a 3-phase 5-levels diode clamped multilevel inverter using MATLAB Simulink and MOSFET as the switching device and PWM technique as the pulse generator, then comparing the MOSFET and transistor as switching device. Based on simulation results, design of 3-phase 5-levels diode clamped multilevel inverter system has a good performance by using MOSFET as switching device than using IGBT and also has smooth signal after filtered by 2nd order low pass filter. Keywords: Multilevel inverter, diode clamped, IGBT, modulation, MATLAB Simulink